A Principles – Based Assessment of The Quality of Zimbabwe’s Direct Tax Policy for The Digital Economy - Jeffry Tatendashe Ndhlovu (Universitas Airlangga, 2023)
Background: In 1998, under the Ottawa framework, the OECD and non-OECD countries agreed that any new taxation rules should adhere to the guiding principles, namely Neutrality, efficiency, certainty and simplicity, effectiveness, fairness flexibility (Cockfield, 2006). In the absence of an international consensus-based – taxation framework for the digital economy, a question arises on whether unilateral measures adopted by countries such as Zimbabwe comply with the principles of a good tax policy. Objective: The study aimed to examine the quality of Zimbabwe's direct tax policy for the economy based on the principles of a good tax policy prescribed by the Organisation for Economic Cooperations and Development (OECD). Method: The study was carried out under a pragmatic philosophical view and adopted a quantitative cross-sectional survey as the research design. Data collection was done using closed-ended questionnaires. The study population comprised 250 tax experts drawn from the Zimbabwe Revenue Authority (ZIMRA) representing tax administrators and private sector tax practitioners representing the taxpayers. Quantitative data was collected from a sample of 146 respondents. Systematic random sampling was used to select the respondents. Chi-squared test was used to analyze the data in SPSS. Results: The study revealed that among the overarching principles of a good tax policy, namely (1) Fairness; (2) Certainty and Simplicity; (3) Neutrality; (4) Efficiency, and (5) Effectiveness, Zimbabwe's tax policy for the digital economy only complies with the principles of Fairness, Certainty and Simplicity. Conclusion: The study established that, to a greater extent, Zimbabwe's tax policy for the digital economy needs to comply with the principles of a good tax policy. Keywords: digital economy; OECD, principles; taxation; Zimbabwe